Enhancing societal wellbeing, Islamic transformation centre and network-of-mosque: a conceptual solution - Ahmad Dahlan, Abdul Rahman; Nasution, Ammar Ihsan; Husaini, Muhammad Iqbal; Ahmed, Mohamed Hassan (2015)
Lessons learnt from the history of Prophet Muhammad saw and his companions in harnessing mosques to provide holistic and value-added services such as community, education, businesses, advisory and halal center for the purpose of society wellbeing. Today, mosques are at every nook and corners in Malaysia, but the functions of the Mosque are limited and are used for specific religious and spiritual purposes. Thus, this conceptual program will develop the Islamic T r a n s f o r ma t i o n Center (ITC) through t h e Network- of-Mosque (NoM). Harnessing on the NoM capabilities, mosques can be used as a center for transformation which provides value-added services to the society. These services will include community classes, marriage services, zakat collection and distribution, promoting halal center, sermons and Islamic learning and education hub. Also with NoM, Mosque can be used for medical clinic, home for the poor and the travelers, and eating place for the hungry and needy. This conceptual program introduces to improve the quality of service through strategic partnership between government, industry, and society which will result to raise the entrepreneurs and lead to the prosperity. This program demands for Quadruple Helix Model (QHM) collaboration which involves the Government, Academia, Industry, and Citizen as the main actors for this program. Nine blocks of Business Model Canvas (BMC) framework and literature review used as the methodology for this paper. To achieve its goals, this program consolidates and synergizes the initiatives of government agencies based on the Whole of Government (WoG) approach. The findings of this paper show that the Mosque can facilitate the development and sustainability of ITC functions that serve the public and citizens better by harnessing the NoM potential and capabilities.